Meningkatkan Kinerja Anggaran Daerah melalui Efisiensi Proses: Peran Kapabilitas Digital, Standarisasi, dan Integrasi Data - Novly G. Wowiling; Agus S. Soegoto; Joubert Barens Maramis; Hendra N. Tawas (Jurnal Riset Akuntansi, 2026)
Regional budget performance is an important indicator in assessing the effectiveness of public financial management. However, various regional governments still face problems such as low budget absorption, delays in program implementation, and suboptimal information system integration. This study aims to analyze the influence of digital capabilities, process standardization, and data integration on regional budget performance through process efficiency in the North Minahasa Regency Government. The study used a quantitative approach with an explanatory research design. Data were obtained from 120 State Civil Apparatus (ASN) involved in regional financial management and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that digital capabilities, process standardization, and data integration had a positive and significant effect on process efficiency. Furthermore, these three variables and process efficiency were proven to have a positive and significant effect on regional budget performance. Process efficiency also acts as a partial mediator in the relationship between digital capabilities, process standardization, and data integration with regional budget performance. These findings indicate that improving budget performance is not only determined by the use of digital technology, but also by the organization's ability to implement standardized procedures, integrate data, and create efficient work processes. This research contributes to the development of public sector digital transformation literature and provides input for local governments in improving the effectiveness of regional financial management